(untitled) (Research, Society and Development, 2020)
This is a bibliographic research with a qualitative approach and descriptive character whose object of study is the role of the family doctor in the home visit, which aimed to describe the practices developed by family doctors in the context of the home visit of the Family Health Strategy. As a methodology, the Virtual Health Library was used, in the LILACS, BDENF, MEDLINE and SCIELO information bases, with a time frame from 2009 to 2018. As the family doctor has the opportunity to accompany this user and his family , the home visit (HV) can become a space that provides interaction and dialogue, overcoming the technical issue, exclusively. It concludes the importance of the family doctor as an educator and advisor in health promotion, since it is the professional who has technical knowledge and skills to perform a detailed analysis of the conditions of the elderly client and their caregiver.